MANAGEMENT OF MAGNESIUM IMBALANCE IN THE PEDIATRIC INTENSIVE CARE UNIT - YU.V. BYKOV; A. N. OBEDIN; V.V. FISCHER; E.V. VOLKOV; O.V. ZINCHENKO; A.A. MURAVYOVA; I.V. YATSUK (Паёми Сино)
A review of the literature regarding magnesium (Mg²⁺) imbalance in children and adolescents in intensive care unit settings was conducted. The search for relevant information was performed using the Cochrane Library, PubMed, ScienceDirect, and Medscape databases, with keywords such as "magnesium", "hypomagnesemia", "hypermagnesemia", "children", "adolescents", and "intensive care". The review included sources published